Quelle cohérence pour la politique française de filières ? Les décalages entre la filière solidaire telle qu’elle devrait être et ce qu’elle est - Samuel Klebaner; Guillaume Assogba (Revue de la Régulation)
This article aims to investigate the relevance of the new French policy of “filière”. By using the institutional political meso-economics point of view, we highlight a gap between the latest French policies for structuring industries into filieres and the objective pursued by such policies. Our demonstration is organized as follow. First, using the institutional meso-economics view, we’ll provide a theoretical definition of the filiere as a particular set of industries technologically closes, structured by political measures aiming to create solidarity among stakeholders. Second, we introduce the instruments used by public authorities within the definition of filiere policies. Finally, we show some shortcomings of such policies, in questioning the coherence of the filières, through recent controversy especially in the automotive industry.